Facial Soft Tissue Repositioning With Neuromodulators: Lessons Learned From Facial Biomechanics. (13th April 2022) - Hernandez, Claudia A; Davidovic, Kristina; Avelar, Luiz E T; Alfertshofer, Michael; Freytag, David L; Frank, Konstantin; Moellhoff, Nicholas; Bihun, Rebekah; Green, Jeremy B; Cotofana, Sebastian
Abstract: Background: Neuromodulators have proven efficacy in reducing facial rhytides and have also been reported to improve jawline contour and the appearance of platysmal bands. Lifting effects of the tail of the eyebrow are expected outcomes when targeting the lateral periorbital region, underscoring the versatility of neuromodulator treatments. Objectives: The aim of this study was to analyze the clinical effectiveness of a novel neuromodulator-based injection algorithm with regards to its ability to reposition the middle and lower facial soft tissues. Methods: Seventy-five study participants (8 males, 67 females) with a mean [standard deviation] age of 37.5 [8.5] years were injected with neuromodulators in the subdermal plane of the mandibular soft tissues following a standardized algorithm. Live rating of clinical appearance was performed, as well as volume change and skin vector displacement measured by 3-dimensional imaging at baseline, Day 14, and Day 30. Results: Three-dimensional volume analysis revealed an increase in midfacial volume by 0.46 mL, and a decrease of the lower facial volume by 0.30 mL compared with baseline. Additionally, an improvement of midfacial fullness (by 0.13) and jawline contour (by 0.44) was reported on clinical rating scales at Day 30 compared with baseline. Conclusions: Facial soft tissues can be repositioned during the 30-day follow-up period following a neuromodulator treatment; this was reflected through an increase in midfacial volume as well as through a decrease in lower facial volume. The novel injection algorithm presented can provide a safe and effective option for patients desiring improvement of midfacial fullness and jawline contour with neuromodulator treatment alone. Level of Evidence: 4: